Shaking table test on seismic performance of continuous rigid frame bridge with cast-in-place and fabricated super high piers. (December 2022) - Wang, Shaojian; Xu, Weibing; Wang, Jin; Huang, Xiaomin; Sun, Hang; Ma, Jun; Chen, Yanjiang
Abstract: The seismic performance of a continuous rigid frame bridge with cast-in-place or fabricated super high piers (CRFB-CSP or CRFB-FSP) is still in the exploratory stage. In this study, four 1/20 scaled models of a main CRFB-CSP, CRFB-FSP, and two adjacent bridges (AB) are designed and manufactured. By considering the longitudinal direction as an example, the seismic performance of CRFB-CSP and CRFB-FSP under the action of non-long-period (NLP), non-pulse-like long-period (NPLP), and pulse-like long-period (PLP) ground motions is studied through a shaking table test; in particular, the impact of pounding between the main bridge (MB) and AB is considered. The results show that both CRFB-CSP and CRFB-FSP reflect higher-order mode participation (HMP) characteristics with and without pounding conditions. The influence of HMP on the seismic response of the CRFB-CSP and CRFB-FSP increases as the ground motion intensity increases. The HMP of the CRFB-FSP is more significant than that of the CRFB-CSP. After considering the pounding, the influence of the HMP increases significantly under the PLP ground motion. Moreover, the peak pounding force ( Pf ) between the MB and AB is higher under PLP and NPLP ground motion excitations. Additionally, Pf is greatest when the velocity pulse period is close to the first-order vibration period of the MB. The Pf value between CRFB-FSP and AB is greater than that between CRFB-CSP and AB. After considering the pounding, the longitudinal peak displacements of the main beams of the CRFB-CSP and CRFB-FSP decrease. Pounding usually increases the horizontal and vertical acceleration responses of the main beam and pier top of the CRFB-CSP and CRFB-FSP, which may have a significant impact on the failure mode of the CRFB-FSP piers.